Curvas de Preston para Minas Gerais 1991-2010: evolução regional e o papel do Programa de Saúde da Família - Philipe Marques Carvalho Maciel (2015)
The debate regarding the determinants of population health is a long and still open one. An important part of this debate concerns the relative roles of income and public policy to the evolution of life expectancy. This dissertation touches upon a part of this discussion, analyzing the increase of life expectancy at birth in Minas Gerais and its health regions between the years of 1991 and 2010. Through the so-called Preston curves it decomposes the relative contribution of income and public policy to the life expectancy increase that took place during these years and also describes the behavior of the regional heterogeneity in health production in the same time frame. It finds out that public policy was the main factor behind the increase of life expectation, explaining around 60% of the observed evolution. It also finds that the regional Preston curves have converged during the covered period, being evidence of a reduction of public policy disparities. However, when evaluating the possible role of the Programa de Saude da Familia, a primary health care program and an important public policy innovation devised during the covered period, it did not find evidence that it was relevant to health production in that time span.